STUDI PERILAKU KESELAMATAN BERKENDARA PADA PENGENDARA SEPEDA LISTRIK DI KOTA PALANGKA RAYA - AUDRY SEBASTIAN INDRAJAYA (INFO-TEKNIK, 2025)
The increasing use of electric bicycles as eco-friendly transportation in Palangka Raya City presents unique challenges related to riding safety. This study aims to analyze the safety behavior of electric bicycle riders, identify the dominant factors influencing such behavior, and determine the age group most responsible for safe riding practices. A quantitative survey method employing an Analytical Hierarchy Process (AHP)-based questionnaire involving 20 experts and experienced users was utilized. The results indicate that accident risk is the most significant concern (42%), followed by risky behavior (34%) and safety behavior (24%). The adult age group (26–45 years) demonstrates the best safety behavior with a global weight of 49%. These findings highlight the importance of continuous education and regulatory enforcement to enhance electric bicycle rider safety. Recommendations emphasize the role of authorities, academics, and the community in optimizing traffic safety policies and awareness.